Perancangan Aplikasi Tumbuh Kembang Anak: Perancangan Aplikasi Tumbuh Kembang Anak (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2025)
Changes in lifestyle due to increasing economic demands have caused many parents, especially working mothers, to have limited time to monitor their children’s growth and development. This condition also occurs at Piony Daycare, which still uses a manual recording system for reporting child growth and development, potentially causing delays and unintegrated data. This Community Service Program (PKM) aims to design and implement a web-based child growth monitoring application that can be used by caregivers, professional staff, medical personnel, and parents. The implementation method includes direct mentoring, Focus Group Discussions (FGD), application usage training, and evaluation through pre-tests, post-tests, and in-depth interviews. The results show that the application’s implementation brought significant improvements to the child growth reporting system. The recording process became faster, more accurate, and accessible in real-time to parents. Respondents stated that the application facilitated reporting, improved work efficiency, and strengthened communication between the daycare and parents. In conclusion, the implementation of the web-based digital system at Piony Daycare enhanced documentation effectiveness and transparency in child growth reporting and has the potential to serve as an innovative service model for similar institutions in the future.
Keywords: Digital Application; Child Development; Daycare; Digital Reporting; Community Service